Exploitation and development of mineral resources - The environmental perspective - Katiyar S.C.; Sachan P.C.; Pandey K.K.; Mishra B.P.; Upadhyay S.N. (My University, 2025)
India must look for a symbiosis of the economic and environmental goals of mineral exploitation as well as conservation and recycling by persuing the useful consumption concept. The concept of useful consumption of mineral resources, minimizes environmental degradation while allowing for continued use and conservation. If we are careful in mining, transporting, manufacturing and recycling of our mineral resources we may be able to use natural ecological processes in ecosystems and biosphere to aid in waste recycling and disposal. These public service functions of ecosystems and the biosphere are important components of the total utilization of resources.